2022
DOI: 10.3390/md20070412
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Galactofucans: An Outstanding Class of Fucoidans with Promising Bioactivities

Abstract: Fucoidans encompass versatile and heterogeneous sulfated biopolysaccharides of marine origin, specifically brown algae and marine invertebrates. Their chemistry and bioactivities have been extensively investigated in the last few decades. The reported studies revealed diverse chemical skeletons in which l-fucose is the main sugar monomer. However, other sugars, i.e., galactose, mannose, etc., have been identified to be interspersed, forming several heteropolymers, including galactofucans/fucogalactans (G-fucoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 140 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…The high ratio of glucose in L. saccharina _MAE confirmed the high sugar content shown in Table 2 . Additionally, the absence of glucose in F. vesiculosus _MAE indicated its galactofucan nature and might propose a superior bioactivity compared with the other fucoidans of the current study [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high ratio of glucose in L. saccharina _MAE confirmed the high sugar content shown in Table 2 . Additionally, the absence of glucose in F. vesiculosus _MAE indicated its galactofucan nature and might propose a superior bioactivity compared with the other fucoidans of the current study [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds are known to show specific activity against cancer and tumors [ 65 , 66 ]. Additionally, the monosaccharide composition indicated that the F. vesiculosus _MAE fucoidan belongs to the sulfated galactofucans which are characterized by their outstanding and potential bioactivities [ 22 ]. Hence, the bioactivity of phenolic residuals and sulfated galactofucan skeleton might explain the higher cytotoxic behavior against MCF7 and Caco-2 cell lines of F. vesiculosus _MAE compared with the other fucoidan fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type is found in the order Fucales, including, for example, Fucus evanescens, F. vesiculosus and F. serratus (Bilan et al, 2002;Ale & Meyer, 2013), whereas fucoidans from species of the order Laminariales, for example Saccharina latissima, have a backbone composed mainly of �(1!3)-linked l-fucosyl moieties (Bilan et al, 2010). A third type, known as sulfated galactofucans (Zayed et al, 2022), are found in various Fucales species prevalent in the Pacific, Western Pacific (South China Sea) and Indian Oceans, for example Turbinaria ornata, Sargassum mcclurei and S. oligocystum, and have a backbone containing both l-fucosyl and d-galactosyl residues (Zvyagintseva et al, 2021). In all types of fucoidans the l-fucosyl moieties may be substituted with sulfate (-SO À…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the pharmacological properties of secondary metabolites and other bioactive substances in marine macroalgae have been reviewed by Priyanka et al [ 8 ], emphasizing their antimicrobial, antitumor, anti-inflammatory, antidiabetic, antiprotozoal, antiviral, and antioxidant activities. Zayed et al [ 9 ] reviewed the biogenic sources and outstanding bioactivities of galactofucans/G-fucoidans, giving insights into the possibilities of novel drug discoveries. The current review focuses on the structure, chemical composition, extraction and purification of fucoidan from the marine brown macroalgae.…”
Section: Introductionmentioning
confidence: 99%